Liver fibrosis scores and atrial fibrillation incidence in heart failure with preserved ejection fraction. (22nd August 2022) - Liu, Xiao; Chen, Wenya; Shao, Wen; Jiang, Yuan; Cao, Zhengyu; He, Wanbing; Wu, Maoxiong; Chen, Zhiteng; Ma, Jianyong; Chen, Yangxin; Yu, Peng; Zhang, Yuling; et al.
Abstract: Aim: Non‐alcoholic fatty liver disease (NAFLD)‐related advanced liver fibrosis (Stage 3 or 4) was reported to be linked to worse prognosis in patients with heart failure with preserved ejection fraction (HFpEF). This study aims to assess the relationship between liver fibrosis scores and new‐onset atrial fibrillation (AF) incidence in patients with HFpEF in the Treatment of Preserved Cardiac Function Heart Failure with an Aldosterone Antagonist (TOPCAT) trial. Methods and results: Baseline liver fibrosis levels, assessed by NAFLD fibrosis score (NFS) or Fibrosis‐4 index (FIB‐4), with AF incidence were expressed as hazard ratios (HRs) using the Cox proportional hazard model. The risk for advanced fibrosis was estimated to be 21.5% (447/2072) as assessed by FIB‐4 (>3.25) and 4.2% (88/2072) as assessed by NFS (>0.676) in HFpEF patients without baseline AF. After a median follow‐up of 3.11 years, 106 new‐onset AF cases occurred. In multivariate analysis, elevated NFS [NFS = −1.455–0.676: HR 2.44, 95% confidence interval (CI) 1.27–4.68; NFS > 0.676: HR 3.36, 95% CI 1.27–6.80; per 1 unit increase: HR 1.15, 95% CI 1.01–1.32], not FIB‐4 (FIB‐4 = 1.45–3.25: HR 1.02, 95% CI 0.67–1.55; FIB‐4 > 3.25: HR 1.69, 95% CI 0.76–3.79; per 1 unit increase: HR 1.13, 95% CI 0.93–1.37), was associated with increased AF incidence. The NFS (C‐index 0.662), not FIB‐4 (C‐index 0.531), had a moderate predictive ability in predicting incident AF. Conclusions: Among patients with HFpEF, the risk of advanced liver fibrosis is associated with an increased incidence of new‐onset AF and may be a novel predictor for new‐onset AF. Additional studies are needed to confirm our results.